MEETING REPORT: UNESCO-MERCK AFRICA RESEARCH SUMMIT 2015- ACCELERATING ACCESS AND SUSTAINING INNOVATION 'FROM AFRICA FOR AFRICA'. - Omange, R.W.; Ocholla, A.O; Kwallah, A.O; Kageha, S. N; Mwangi, J.; Cherutich, R. K; Odeny, T.A.; Nzomo, T.; Angwenyi, S.; Yonga, P.; Kariuki, F.; Kyalo, M.; et al. (African Journal of Infectious Diseases (AJID), 2016)
Background: The Ebola virus disease outbreak of 2014 was the largest, longest and most devastating in the history of the disease. It demonstrated the social and economic impact an emerging infectious disease can have in a globalized world. Health systems in affected countries were stretched to the point of near collapse, while social relations and traditional practices were negatively impacted. Heads of African research institutions, African government representatives, leaders of global pharmaceutical companies, global infectious disease experts and close to 100 young African researchers from 25 countries; Assembled in Geneva on 19 and 20th October 2015, for the inaugural UNESCO-Merck Africa Summit sponsored by the United Nations Educational, Science and Culture Organization and Merck KGAGoal of Summit: The primary goal of the summit was to develop strategies to increase health research capacity in Africa, with special focus on Ebola and enhancing pandemic preparation for emerging infectious diseases. The summit was also provide a forum to showcase the research taking place in Africa, and provided platform for African researchers to network. Some of the key issues discussed included; strategies for enhancing policy frameworks to promote knowledge translation, strengthening of health systems, enhancing knowledge and data sharing, and increasing innovation in Africa.Conclusions: Summit attendees recognized that Africa still bore the heaviest burden of infectious disease, and increased commitment by African governments to fund health research, offered the best hope for developing health solutions and interventions to improve the health of Africans. Improved health in turn would enhance the productivity of Africans, further supporting the socio-economic transformation currently taking place on the continen